Implementation of Islamic Religious Values on Students' Religious Behavior at SMP Negeri 1 Sambas - Sas Yunita; Arnadi Arnadi; Aslan; Mohd Faeez Ilias (CV PUTRA PUBLISHER, 2025)
This research stems from the phenomenon of moral decline among the community, especially in the world of education. This is a negative result of the development of science and technology. Therefore, Islamic values must be instilled in students through education as their provision in the future. The focus of this research is: 1) How is the process of implementing islamic teachings values against the religious behavior of students of SMP Negeri 1 Sambas? 2) What are the implications of the implementation of Islamic religious values on the religious behavior of SMP Negeri 1 Sambas students? This study uses qualitative shortness and descriptive research types. Data collection techniques with interviews, observations and documentation. Data analysis using data reduction, data presentation and conclusion/verification withdrawal. The results showed the following: 1) The process of implementing islamic teachings in Sambas State Junior High School is carried out continuously through intracurricular, cocurricular and curricular activities using methods of understanding, advice, exemplary and punishment; 2) The implications of the implementation of islamic teachings on students' Religious Behavior are: (a) increasing students' understanding and knowledge of islamic teachings; (b) raise awareness of students to always worship; and (c) bring about a change in students' religious attitudes and behaviors in a better direction.